PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SEKOLAH DASAR - azizah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
The background of this study is the low absorption of learners, especially in grade V SDN 019 Bumi Ayu study result of low student science. This can be seen from the students score in the middle of the average value of only 61.5. The percentage of students who reach the KKM is only 50% out of 20 students, and the total number of completed students is only 10 people. This research is a classroom action research conducted on Grade V student of SDN 019 Bumi Ayu. The results obtained data Activity teachers reached 41%. At the second meeting also reached 54%. Meanwhile, after the second cycle increased at the third meeting with a percentage of 66%. At the fourth meeting with a percentage of 75%. While the activity of students on the first cycle of the first meeting with a percentage of 41% At the second meeting with a percentage of 58% in the second cycle of student activity with a percentage of 70%. The 4th meeting was a percentage of 79%. The result of science learning of grade V students on the basic score is 50% of the total students, whereas in daily test I students reach KKM to 60% of the total students, and in daily test II the number of students reaching KKM increased to 80%. Similarly, in the initial data the average value of 61.5 cycles I increased with the average student score 67 and cycle II with the average score of 72.25 students